Capital Market Issuer Selection Optimization Based on Fundamental Aspect using Dynamic Programming Algorithm - Sutedy, Stanley; Hansun, Seng (Pusat Penelitian Informatika - LIPI, 2016)
The research conducted by the author discuss about the optimization of the selection of capital market issuers by counting each financial variables. These variables are called multiple constraints. In simple fundamental analysis, fundamental value of company is reflected in the values of financial ratios. This optimization uses Dynamic Programming algorithm for selecting the optimal solution of issuers of capital market. Optimization made for issuers that have the same business areas. With this optimization, the user simply need to enter the values of the financial ratios and performed optimization process that will ultimately result in the optimal solution.